Minimizing voltage losses in Sn perovskite solar cells by Cs2SnI6 passivation - Jin Hyuck Heo; Sang Woo Park; Hyong Joon Lee; Jin Kyoung Park; Sang Hyuk Im; Ki‐Ha Hong (EcoMat)
Abstract Stability and oxidation are major bottlenecks in improving the performance of Sn‐based perovskite solar cells. In this study, we present the formation of an n‐type Cs2SnI6 double‐perovskite (Sn‐DP) layer on a (PEAI)0.15(FAI)0.85SnI2 perovskite (Sn‐P) layer using an orthogonal solution‐processable spray‐coating method. This novel approach achieves a minimized Voc loss of 0.38 V and a PCE of 12.9% under 1 sun conditions. The n‐type DP layer effectively passivates tin vacancies, suppresses Sn2+ oxidation, reduces defects, and enhances electron extraction. Furthermore, the Sn‐DP/Sn‐P‐based solar cells exhibit excellent light‐soaking stability for 1000 h in the air under continuous one sun illumination, which is attributed to the stable Sn4+ state of the DP layer. Our experimental and theoretical investigations reveal that the type‐II band alignment between Sn‐DP and Sn‐P enhances the stability of the solar cells. The proposed Sn‐DP/Sn‐P architecture offers a promising pathway for developing Sn‐based solar cells.